Surface and synoptic features of leading and parallel stratiform mesoscale convective systems - Steinweg-Woods, Jesse Matthew, author; Johnson, Richard H., advisor; Rutledge, S. A. (Steven Allan), committee member; Ramirez, Jorge A., committee member (Colorado State University. Libraries, 2010)
This study investigates the surface wind, pressure, and temperature patterns associated with mesoscale convective systems meeting the classification of leading or parallel stratiform. Cases were surveyed over the period of 2002 to 2007 inside the state of Oklahoma. Thirteen leading stratiform cases and ten parallel stratiform cases were identified. The synoptic environment these cases developed in was also investigated and compared to previous studies. The Oklahoma Mesonetwork is utilized to examine the surface features associated with these cases. Mesoscale contributions were isolated through filtering of these data in order to focus on fine-scale features. Streamlines, surface pressures, potential temperatures, and equivalent potential temperatures were analyzed through this method. The study concluded that leading and parallel stratiform systems had similar synoptic environments to previous studies, with some minor differences. Leading stratiform systems were more dependent on low-level jet influence than parallel stratiform systems were. Both system types also formed in the warm sector of a frontal system along its boundary, which typically was a warm or stationary front. These systems also tended to be located in the outer edge of the right entrance region of jet streaks. Leading stratiform systems had a surface pressure pattern very different from trailing stratiform systems. It was found that, in leading stratiform systems, a mesohigh formed behind the main convective region, and a mesolow formed ahead of the stratiform region. Parallel stratiform results were more inconclusive due to a lack of quality cases, but one case showed a surface pressure pattern almost identical to asymmetrical trailing stratiform systems. Maxima and minima of potential and equivalent potential temperatures tended to be located in the same areas, with lower temperatures near mesohighs and higher temperatures near mesolows. It is possible that a leading inflow jet is causing the surface pressure to decrease ahead of the stratiform region in leading stratiform systems. This needs to be confirmed in future study by investigating the vertical wind profile of these systems and validate the presence of this jet.
Keywords: Convection (Meteorology) -- Oklahoma; Atmospheric circulation -- Oklahoma; Precipitation forecasting -- Oklahoma; Mesometeorology -- Oklahoma